Calculation and prediction of the strength of multilayer polymeric reinforced pipes - S. V. Shalyapin; I. V. Gvozdev; I. D. Simonov-Emelyanov (Тонкие химические технологии)
The authors propose a variant of the design and strength calculation for multilayer polymer-reinforced pipes, as well as a methodology to assess long-term strength based on international experience in plastic pipe industry.